Influence of the solvent in low temperature glycosylations with O-(2,3,5,6-tetra-O-benzyl-β-d-galactofuranosyl) trichloroacetimidate for 1,2-cis α-d-galactofuranosylation - Gola, Gabriel Francisco (2011)
Glycosylation studies for the construction of 1,2-cis α-linkages with O-(2,3,5,6-tetra-O-benzyl-β-d-galactofuranosyl) trichloroacetimidate (1) and several acceptors, including d-mannosyl and l-rhamnosyl derivatives were performed. The reactions were conducted at low temperatures using CH 2Cl2, Et2O, and acetonitrile as solvents. A non-participating solvent such as CH2Cl2 at -78 °C, favored the α-d-configuration. In contrast, acetonitrile strongly favored the β-d-configuration, whereas no selectivities were observed with Et 2O. The use of thiophene as an additive did not enhance the α-d-selectivity as in the pyranose counterpart. Although selectivities strongly depended on the acceptor, trichloroacetimidate 1 constitutes a valuable donor for the synthesis of α-d-Galf-(1→2)-l-Rha and α-d-Galf-(1→6)-d-Man. As these motifs are present in pathogenic microorganisms, these procedures described here are useful for the straightforward synthesis of natural oligosaccharides.